2023
DOI: 10.1111/bjh.18680
|View full text |Cite
|
Sign up to set email alerts
|

The Rory Morrison WMUK Registry for Waldenström macroglobulinaemia: The growth of a national registry for a rare disorder

Abstract: Summary National registries are used globally to characterise patient demographics, treatment choices and mortality to inform and improve clinical management. Waldenström macroglobulinaemia (WM) is a rare, treatment‐responsive B‐cell lymphoproliferative disorder with diverse clinical features and variable outcomes. To prospectively chart changes in the management of WM in the UK, the Rory Morrison Registry (RMR) was developed to systematically collect real‐world data. Here we describe the development of the RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Other cohorts that are not screened report a lower proportion. The national WMUK Rory Morrison Registry of >1300 patients identified a prevalence of 7% 11 although this excludes those with other NHL. A Greek cohort of 595 patients with WM identified 5.5% with cryoglobulins 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Other cohorts that are not screened report a lower proportion. The national WMUK Rory Morrison Registry of >1300 patients identified a prevalence of 7% 11 although this excludes those with other NHL. A Greek cohort of 595 patients with WM identified 5.5% with cryoglobulins 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The Rory Morrison Registry is a national comprehensive data repository in the UK developed to ascertain real‐world data for patients with WM and its associated disorders [ 6 ]. Research ethics approval was obtained from the London—South East Research Ethics Committee (REC: 17/LOLO/1666).…”
Section: Introductionmentioning
confidence: 99%
“…They contained 58 questions and were distributed digitally on a quarterly basis to patients registered for PROMs. The discrepancy between the large denominator of patients on the registry with clinical data and the small number of PROM entries relates to the different routes of enrolment—the former through enrolment of clinical centres [ 6 ] and the latter via the direct recruitment of patients who specifically registered and consented for PROMs. Here, we reviewed the results from a snapshot of PROM questionnaires used to assess patient QoL in WM.…”
Section: Introductionmentioning
confidence: 99%
“…4 Using two questionnaires, this study showed that 10% of patients present stress levels identical to that of post-traumatic stress disorder and better QoL scores in patients treated with Bruton tyrosine kinase inhibitor. In their paper, Uppal et al 1…”
mentioning
confidence: 98%
“…In their paper, Uppal et al 1 describe the different steps of the development of the Rory Morrison Registry (RMR), the UK registry for WM and IgM‐associated disorders, and present the first results on demographics, treatments and outcomes. Among the preliminary results reported, the authors point out the significant proportion of young patients (37% aged <60 years).…”
mentioning
confidence: 99%